Boussinesq equations: M-fractional solitary wave solutions and convergence analysis - Sulaiman, Tukur Abdulkadir; Bulut, Hasan (Elsevier, 2019)
The studies of the dynamics behaviors of nonlinear models arising in ocean engineering play a significant role in our daily activities. This study investigates the nonlinear fractional modified Boussinesq equation and the fractional bad Boussinesq equation using the extended sinh-Gordon equation expansion method. Several travelling wave solutions are successfully constructed. By choosing suitable values of parameters, the 2D and 3D graphs of the reported solutions are successfully plotted. The convergence analysis of the applied method is also discussed. (C) 2018 Shanghai Jiaotong University. Published by Elsevier B.V.
Keywords: The Sinh-Gordon equation; Boussinesq equations; Solitons; M-fractional derivative; Convergence analysis